Development of OXY111A, a novel hypoxia-modifier as a potential antitumor agent in patients with hepato-pancreato-biliary neoplasms - Protocol of a first Ib/IIa clinical trial. Issue 1 (December 2016) - Limani, Perparim; Linecker, Michael; Kron, Philipp; Samaras, Panagiotis; Pestalozzi, Bernhard; Stupp, Roger; Jetter, Alexander; Dutkowski, Philipp; Müllhaupt, Beat; Schlegel, Andrea; Nicolau, Claude; Lehn, Jean-Marie; et al.
Abstract Background Solid tumors, such as hepato-pancreato-biliary cancer, develop tumor hypoxia with tumor growth. Despite advances in surgery, a majority of these patients are in an unresectable condition. At this stage standard cytotoxic chemotherapy regimens are applied with limited success. Novel biological treatment options based on an antiangiogenic mechanism of action neglect other hypoxia mediated mechanisms (e.g. epithelial-mesenchymal transition, Warburg effect, and immunological response) leading to an increased invasiveness with a poor outcome. The novel antihypoxic molecule myo-inositoltrispyrophosphate (ITPP, OXY111A) acts as an allosteric effector of hemoglobin and promotes normoxia in hypoxic tumors. In preclinical studies, tumor growth was reduced and survival prolonged. Additionally, a beneficial side effect profile was observed. Methods In this first Ib/IIa clinical trial we will assess safety and tolerability of OXY111A as well as a proof of concept regarding efficacy in patients with non-resectable primary and secondary tumors of the liver, pancreas, and biliary tract. The study design is exploratory, prospective, open-labelled and mono-centric. The study is divided in a dose escalation part with a maximum of 48 subjects and an extension part, in which 21 subjects will be included. Discussion The novel antihypoxic compound OXY111A has been tested in several cancer animal models showing beneficial effects for both survival and low side effect profiles. This first in patient application of OXY111A will reveal potential beneficial outcomes if anti-hypoxic therapy is added to standard cytotoxic treatment in patients with primary and secondary hepatopancreatobiliary tumors. Trial registration Institution Ethical Board Approval ID: KEK-ZH-Nr. 2014-0374; Swiss regulatory authority Swissmedic (2015DR1009); ClinicalTrials.gov Identifier:NCT02528526, prospectively registered on November 11th, 2014.